Netkit: network emulation for education‡. (16th May 2014) - Pizzonia, Maurizio; Rimondini, Massimo
Summary: In the era of virtualization, virtual networking plays an important role. Besides production use, virtual networking can be effectively adopted in many other contexts where accurate emulation of functionalities is important, like testing before deployment, evaluation of what‐if scenarios, research, and, increasingly, didactics. In this paper, we describe our 10‐year experience in designing, implementing, using, and maintaining Netkit, an environment for simple, inexpensive, and lightweight network emulation targeted at didactics. We analyze the peculiar requirements in this context and discuss how the architecture chosen for Netkit is tailored to fulfill them. We show that Netkit is particularly well suited for a quick preparation of complex network scenarios comprising a wide range of networking technologies. These scenarios can be specified using configuration languages that are similar to those used on real devices and, once set up, can be easily distributed via email or published on the Web. Netkit comes with a rich set of ready‐to‐use pre‐configured networks, accompanied by lecture slides that enable users to immediately experiment with specific case studies. To complete the picture, we report our experience in supporting and fostering the growth of the community of users revolving around Netkit: more than 15 educational institutions worldwide take advantage of Netkit, allowing teachers and students to practice with realistic networks without the need of expensive laboratories. We also detail how we profitably use Netkit within advanced academic‐level networking courses and related examinations at the Roma Tre University. Copyright © 2014 John Wiley & Sons, Ltd.